Prevalence of CYP2C19 and ITGB3 polymorphisms among Bangladeshi patients who underwent percutaneous coronary intervention. (August 2021) - Islam, Md Rabiul; Nova, Tasnova Tasnim; Momenuzzaman, NAM; Rabbi, Sikder Nahidul Islam; Jahan, Ishrat; Binder, Thomas; Islam, Mohammad Safiqul; Hasnat, Abul; Nahar, Zabun
Introduction: Antithrombotic agents are the basic therapeutic option for patients with arterial thrombosis who underwent percutaneous coronary intervention (PCI). In Bangladesh, aspirin and clopidogrel are frequently prescribed as antithrombotics or platelet inhibitors. Studies reported the genetic polymorphisms of CYP2C19*2, CYP2C19*17, and ITGB3 cause an alteration of the pharmacodynamic and pharmacokinetic profile of aspirin and clopidogrel. Therefore, we aimed to assess the prevalence of CYP2C19*2, CYP2C19*17, and ITGB3 polymorphisms among Bangladeshi patients with cardiovascular disease (CVD) who underwent PCI. Methods: Here we assessed a total of 1, 000 CVD patients (male 782 and female 218) who underwent PCI and were treated with clopidogrel and/or aspirin. We performed genotyping of patients treated with clopidogrel and aspirin by polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP) and tetra-primer amplification refractory mutation system PCR (T-ARMS-PCR) methods. The PCR products of clopidogrel-treated patients were screened with agarose gel electrophoresis and then digested with SmaI and NsiI-HF for CYP2C19*2 and CYP2C19*17, respectively. We genotyped aspirin-treated patients with T-ARMS-PCR for missense rs5918 (PlA1/A1) polymorphism of the ITGB3 gene. Then we ran the digested PCR products on 2% agarose gel electrophoresis to detect the mentioned polymorphisms. Results: Among the clopidogrel-treated patients, we observed 64.1% polymorphism (hetero + mutant) of CYP2C19*2 (loss-of-function allele) and 22.7% (hetero + mutant) of CYP2C19*17 (gain-of-function allele). On the other hand, among the aspirin-treated patients, polymorphisms of ITGB3 were 84.1% homozygous (PlA1/A1), 15.6% heterozygous (PlA1/A2), and 0.3% mutant homozygous. Conclusion: In the present study, we observed a high prevalence of genetic polymorphisms of CYP2C19 and ITGB3 genes. Therefore, we recommend genotyping of CVD patients before prescribing clopidogrel or aspirin to prevent coagulation. Based on the genotyping study, the adjustment of doses or alternative generics might require to avoid therapeutic failure or toxicity in some cases.